Assessment of chewing and swallowing in post mandibular resection patients with no bony reconstruction – A cross sectional study - Irfana Sithara Cholayil; Reena Rachel John; Narendran Achuthan (Journal of Oral Biology and Craniofacial Research)
Introduction: The intricate process of chewing and swallowing is compromised following mandibular resection. An evaluation of chewing and swallowing is crucial to comprehend the quality of life following surgery in cases when bone repair was not performed. The purpose of this study is to evaluate chewing and swallowing in mandibulectomy patients without bony reconstruction. Material and method: This study involved ten patients, including four with H defects, three with L defects, and three with LC defects, after a one-year postop period. Using Robbin's penetration aspiration scale, video fluoroscopy was used to evaluate swallowing. Using a functional oral intake scale, chewing was assessed. Fischer's exact test was used for statistical analysis. Results: Robbin's penetration aspiration scale score of 1 was noted in all 10 patients. According to FOIS, 50 % of patients with H defect scored 4, and 66.7 % of those with L defect scored 6. The results were not significant when the scores were correlated with the type of defect. Conclusion: Mandibular surgical defects which were not reconstructed with bone were shown to affect the quality of life in our study. Chewing efficiency was poorest in patients with H defect. Swallowing efficiency was not affected adversely in this group of patients.